Approval Test of Augmented Reality-Based Learning Media on Computer Network Installation Materials - Hendra Sahputra Batubara; Nizwardi Jalinus; Sukardi Sukardi; Waskito Waskito; Agariadne Dwinggo Samala; Fadhli Ranuharja; Army Trilidia Devega; Ika Parma Dewi (Jurnal Teknologi Informasi dan Pendidikan, 2021)
Abstract: This article aims to describe the validity of Augmented Reality learning media on computer network installation materials. This type of research is an R&D (research and development) research, with the ADDIE model approach: Analysis, Design, Develop, Implement and Evaluate. The results of the validity test of the media aspect that were tested on two experts showed that the Augmented Reality-based learning media was declared very valid with the Aiken's V value of 0.827 and the validity test on the material aspects tested on the two experts showed that the Augmented Reality media was claimed to be very valid with the Aiken's V value. is 0.958. Based on the results obtained, the Augmented Reality learning media on the computer network installation material is suitable for use by class X Computer and Network Engineering students at Imelda Private Vocational School Medan. However, it is important to follow up, especially trials of using media in the classroom to determine the effectiveness of Augmented Reality learning media on computer network installation materials. Keywords: Learning Media, Augmented Reality, computer network installation